Learning to write killer apps? Performance improvements in innovations - FAN, Terence Ping Ching (Institutional Knowledge at Singapore Management University, 2012)
Commercially successful but not necessarily high-tech innovations can change the fortunes of firms and the quality of lives of many. This paper argues that while groups of specialists can quickly bring together knowledge from multiple domains in developing and implementing innovative ideas, a typical lack of system-wide perspective would prove to be a constraint over successive innovations. In contrast, a single individual who acquires specialist knowledge in multiple domains would avoid this constraint, but would incur a penalty to acquire knowledge across domain boundaries upfront. This leads to two opposing performance predictions on the performance of successive innovations: an increasing trend at a decreasing pace for the former and a J-shape for the latter. Moreover, experience developing solo innovations strengthens the performance for subsequent group innovations. These hypotheses are supported by empirical data on the download performance of third-party software applications written for use within the Facebook social networking context.